Preconditions for adoption inflation targetion - Gathoni, Anthony Gathogo (KDI School, 2011)
In the past decades, the monetary policy encountered by most of the low-income economies has been depressing, this has resulted to extreme periods of monetary instability, vacillating from high inflation, to colossal capital flight, and thereby leading to the downfall of many financial systems. However, the forecast for successful monetary policy transformation in the majority of these countries has been remarkable in forecasting future inflation expectations. This paper provides a theoretical and empirical framework analyzing preconditions that relate to low-income countries and emerging markets likelihood of adopting inflation targeting framework in a sample that comprises both inflation targeters and non-targeters countries covering a period of 1990-2009. The panel data model protracted for analysis will comprise both macro-economic variables and institutional arrangements plausible for the adoption of inflation-targeting framework for these countries. The findings have indicated that, the decision to forge towards IT-framework requires resolute efforts and support in addressing the main drawbacks that may hinder successful implementation of IT-framework to a larger extent on the technical aspects and capability of most of low-income as well as emerging countries, which are limited or lacking.
Thesis(Master) --KDI School:Master of Public Policy,2011